Organizational climate and teaching performance in the educational institution N ° 7088 "Vice-Admiral Gerónimo Cafferata Marazzi", Villa María del Triunfo, Lima 2020. - Sancho Paredes, Marlene (2021)
Studies on organizational climate and teaching performance in educational institutions have special relevance for the quality of regular basic education, which emerges as a revealing problem. This study had the objective: to determine the relationship between the organizational climate and teaching performance in the school "Vice-admiral Gerónimo Cafferata" N. 7088 of Villa María del Triunfo in Lima, Peru. With a quantitative approach, it is a non-experimental design, basic type, correlational bivariate and transverse level, which uses two questionnaires as a data collection instrument and whose population and sample was 30 teachers. The study was of a quantitative approach, basic type and non-experimental design, cross-sectional correlational, and used questionnaires for data collection with a population and sample of 30 teachers used Spearman's rho coefficient for the hypothetical contrast. In whose results and discussion we find that there is a moderate and direct significant relationship. Between both variables: the organizational climate and the teaching performance of Educational Institution 7088.